Terapi Minyak Cengkih Kelapa (NYAIH PADI) sebagai Analgesik Alami untuk Mengatasi Nyeri Sistem Muskuloskeletal: Coconut Clove Oil Therapy (NYAIH PADI) to Natural Analgesic for Overcome Pain in the Musculoskeletal System - Noprianty, Richa; Mulyani, Yanyan; Novita, Lia; Lolan, Yosef Pandai; Sarbini, Amida Sriwianti; Fitriani, Dyah Ayu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Mild morbidity due to pain in the musculoskeletal system often occurs in the elderly and is often treated independently using non-pharmacological therapy. Community service aims to provide education and demonstrate pain management using natural analgesics in the form of coconut clove oil (NYAIH PADI) and acupressure therapy. The activity was held in November 2023 in Nyalindung Village, RW 14, Ganjar Sabar Village, Nagreg District, Bandung Regency with 39 participants attending. The activity was carried out in three stages, namely the stage of making NYAIH PADI, then giving the Nordic Body Map (NBM) questionnaire followed by education and demonstrations regarding acupressure therapy and the process of making NYAIH PADI. Next, the product was distributed to participants who experienced joint pain to be used for one week at a dose of 1 – 2 drops per day on the painful part of the skin and then the changes in pain were seen. The location of the left foot and right foot where many people complain is very painful. The pre and post-test results showed changes in the category of very sick, decreasing by 1.32, and sick, decreasing by 0.25. Meanwhile, low-level sickness and not-sickness increased to 0.53 and 0.54. Giving NYAIH PADI has been proven to reduce pain so it can be used as an initial alternative for the community. At the end of the session, cadres and the community were given a YouTube link to the production process via https://www.youtube.com/watch?v=__kgIp6E2q4. The activity ended with giving door prizes and group photos.